Plasma trough concentrations of antiretrovirals in HIV-infected persons treated with direct-acting antiviral agents for hepatitis C in the real world. (2nd November 2017) - Tempestilli, Massimo; Fabbri, Gabriele; Mastrorosa, Ilaria; Timelli, Laura; Notari, Stefania; Bellagamba, Rita; Libertone, Raffaella; Lupi, Federico; Zaccarelli, Mauro; Antinori, Andrea; Agrati, Chiara; Ammassari, Adriana
Abstract: Background: Possible drug–drug interactions (DDIs) between antiretrovirals (ARVs) and direct-acting antiviral agents (DAAs) are of some concern. Objectives: To investigate ARV plasma trough concentrations ( C trough ) before and during DAAs in patients treated in the real world. Methods: Single-centre, prospective, observational study including HIV/HCV coinfected persons undergoing DAA treatment. Self-reported adherence was assessed and ARVs C trough measured by HPLC-UV. Blood samples were collected before and after 2 months of DAA treatment. Results: One-hundred and thirty-seven patients were included: 21.2% treated with ombitasvir/paritaprevir/ritonavir ± dasabuvir (2D/3D) and 78.8% with sofosbuvir-based regimens. Suboptimal C trough before and during DAA was found, respectively, in 3 (10.3%) and 3 (10.3%) cases treated with 2D/3D, and 16 (14.8%) and 11 (10.2%) with sofosbuvir-based regimens, even if self-reported ARV adherence was always ≥93%. In 2D/3D-treated patients, median darunavir C trough during DAAs was significantly lower than observed before DAAs [1125 ng/mL (IQR, 810–1616) versus 1903 ng/mL (IQR 1387–3983), respectively] ( n = 5; P = 0.009), with a 40.9% decrease. In the same group, no differences in atazanavir or raltegravir concentrations were found. In patients treated with sofosbuvir-based regimens, C trough of all ARVs were similar before and during DAAs. Conclusions: In the real world of HIV/HCV coinfected patients, ARV plasma concentrations during DAAs were generally not different from those found before anti-HCV treatment. Although assessed in a small number of patients, darunavir concentrations during 2D/3D showed a significant reduction when compared with those found before DAAs. ARV plasma concentrations measurement during anti-HCV treatment may give useful information for managing HIV/HCV coinfected persons receiving treatment for both infections.